2016
DOI: 10.1097/nna.0000000000000302
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Clinical Nurses’ Perceptions of Structural and Psychological Empowerment and Engagement on Their Unit

Abstract: Results show positive correlations between empowerment and perceived engagement among clinical nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 3 publications
8
23
2
2
Order By: Relevance
“…In this study, the sample of nurses was predominantly female, with a partner. These are similar results to other national (12)(13) and international (17)(18) surveys.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the sample of nurses was predominantly female, with a partner. These are similar results to other national (12)(13) and international (17)(18) surveys.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the results showed that nurses have opportunities to learn and grow professionally, within the work environment. Similar results are described in previous studies using the same instrument, reinforcing that the opportunity to learn and grow at work implies the use of personal skills, promoting a sense of selfefficacy and autonomy (17)(18)(19) .…”
Section: Discussionsupporting
confidence: 86%
“…The empowerment and work engagement plays a main role in retention of health care providers in clinical nurses. The results showed that structural empowerment and psychological empowerment perception is interconnected and have positive relationship between structural and psychological empowerment (DiNapoli, O'Flaherty, Musil, Clavelle, & Fitzpatrick, 2016).…”
Section: Literature Reviewmentioning
confidence: 94%
“…In view of the growing economic strains on healthcare systems worldwide, it is a positive aspect that many of the implemented measures do not cost money but personal effort. Under this aspect, it has been shown that especially team members who are subject to directions (in our context, for example, junior physicians in training, nurses, radiology and laboratory technicians) are more engaged with the purpose of their work and quality improvement projects far better if they involve all disciplines that will be concerned by the actions taken [15, 16]. …”
Section: Discussionmentioning
confidence: 99%